Hot water flow and temperature measurement to verify CO2 emission reductions using solar water heating - Ivan A. Hernandez-Robles (Measurement: Energy)
This work focuses on reduction of CO2 emissions study by the use of solar water heaters as well as its verification through the development of the AMS - IJ methodology Solar Water Heating Systems (SWH) V2.0 of the Clean Development Mechanism (CDM) agreement for the accreditation of carbon reductions of the United Nations on Climate Change. This study is essential for the progress and generation of knowledge associated with reducing emissions potential estimations by using solar water heaters. For this, this work measures the ambient temperature, the cold water flow and its temperature in SWH input and the hot water flow and its temperature in its output. The measurements were made at three different edifications and locations. The analysis, statistics and grouping of the historical data obtained from these parameters allowed the author to determine a model to estimate the reduction of emissions by the use of solar water heaters throughout the year. This model considers the impact of the weather seasons during the year. The energy saving potential of 3908 GWh was obtained, which represents a reduction of 0.789 Mton CO2 emissions per year at Guanajuato Mexico. This work contributes to the knowledge and development of new techniques and technologies for measuring and verifying the reduction of emissions from energy consumption in buildings with the aim of promoting more sustainable buildings with a zero energy consumption characteristic and a neutral environmental impact.